High Frequency Litigation: SEC Responses to High Frequency Trading as a Case Study in Misplaced Regulatory Priorities - Sokol, Nathaniel E. (Science and Technology Law Review, 2016)
In 1975, Congress amended the Securities and Exchange Act of 1934, calling for the establishment of a National Market System (“NMS”). The NMS rests on the philosophy that fostering competition between private actors through smart regulation can produce stronger markets and greater innovation than dictatorial mandates and aggressive enforcement. Advances toward this goal have generally arrived only in response to major crises of market confidence or jumps in market technology that critically distort the competitive horizon. Regulators often over-prioritize enforcement against individual bad actors to rein in excesses which they are unequipped to understand or deter. This Note employs High Frequency Trading (“HFT”) as a case study of this misplaced regulatory priority. It examines the rise of HFT, the economics behind its profitability, the controversies it has spawned and the reactions it has elicited from the SEC and its agency peers. Next, this Note highlights how relevant enforcement actions brought by the SEC have only peripherally related to the high frequency nature of the target firms or trading strategies, and have failed to address any of the broader concerns raised by market participants regarding HFT’s impact. The Note evaluates many of the alternative regulation-based levers the SEC has available, and suggests changes in both the culture and operation of the agency.